CUF scaling effect on contact angle and threshold pressure. Issue 4 (4th September 2017) - Ng, Fei Chong; Abas, Mohamad Aizat; Abdullah, MZ; Ishak, MHH; Chong, Gean Yuen
Abstract : Purpose: This paper aims to present experimental and finite volume method (FVM)-based simulation studies on the scaling effect on the capillary contact angle and entrant pressure for a three-dimensional encapsulation process of ball-grid array (BGA). Design/methodology/approach: With the development of various sizes of BGA packages, the scaling effect of BGA model on capillary underfill (CUF) process is investigated together with the influences of different industrial standard solder bump arrangements and dispensing methods used as case study. Findings: The experimental results agree well to the simulation findings with minimal deviation in filling time and similar flow front profiles for all setups. The results revealed that the capillary contact angle of flow front decreases in scale-up model with larger gap height observed and lengthens the encapsulation process. Statistical correlation studies are conducted and accurate regression equations are obtained to relate the gap height to the completion filling time and contact angle. CUF threshold capillary pressures were computed based on Leverett-J function and found to be increasing with the scale size of the package. Practical implications: These statistical data provide accurate insights into the impact of BGA's scale sizes to the CUF process that will be benefiting the future design of BGA package. This study provided electronic designers with profound understanding on the scaling effect in CUF process of BGA, which may be extended to the future development of miniature-sized BGA and multi-stack device. Originality/value: This study relates the flow behaviour of encapsulant to its capillary contact angle and Leverett-J pressure threshold, in the CUF process of different BGA and dispensing conditions. To date, no research has been found to predict the threshold pressure on the gap between the chip and substrate.